The Sanskrit version of Yasna 1-8 - Palladino, Martina. (Leiden ; Boston)
xvii, 672 sayfa
Keywords: “This book contributes to the Multimedia Yasna (MUYA) Project, led by Prof. Almut Hintze of SOAS, by presenting an edition of the first eight chapters of the Sanskrit Yasna. This new edition is accompanied by an English translation and two glossaries. This study aims to provide a framework for Parsi literary production in the Indian context and, at the same time, to relate the Sanskrit text to its Avestan and Pahlavi versions. The special feature of this unique text is that it belongs to the Indian cultural environment while remaining part of the Zoroastrian tradition“ --